【研究計画】氷の変形におよぼす不純物の影響の研究 - 繁山, 航; Shigeyama, Wataru (2016)
氷床の流動を高精度に予測する上で，氷の塑性変形のメカニズムを理解することが重要である．特に氷床の高濃度不純物層では氷の変形が速いことが示されているが，その変形メカニズムは明らかにされていない．氷床における氷の変形は，主に結晶の欠陥（転位）の運動によって生じると考えられ，モデル計算では，この転位運動に基づく流動則（変形速度の計算式）が広く用いられている．一方，高濃度不純物層では，転位運動とは異なるメカニズム（粒界すべり・拡散）も変形に寄与している可能性が示唆されている． 本研究では氷床の高濃度不純物層の速い変形のメカニズムを明らかにするため，アイスコア・人工氷の変形試験と試験片の観察・結晶組織解析を行う．試験片の観察・結晶組織解析には電子顕微鏡を用い，変形の前後における不純物の氷内部での状態や分布，結晶組織の変化を調査する．変形試験結果と詳細な観察・結晶組織の解析から不純物を含む氷の変形メカニズムを理解する． In order to predict flow of ice in ice sheet with high accuracy, understanding mechanism of plastic deformation of ice is important. Especially, deformation of impurity-rich layer has been reported to be faster than the other part in ice sheet, however, the mechanism is still unclear. Generally, deformation of ice in ice sheet is explained by movements of defect of the crystal lattice (dislocation) and flow law (which calculates deformation rate) now commonly used for ice sheet modelling is based on the movement of dislocations. On the other hand, the different mechanisms (grain boundary sliding/diffusion) are also suggested to explain the deformation of the impurity-rich layers. In this study, deformation tests of ice cores and artificial ice, observations/analyses of the crystal texture of the ice will be performed to understand the fast deformation mechanisms of impurity-rich ice. Electron microscope are used for investigations of state/distribution of the impurities and changes in the crystal texture. Combination of the deformation tests and the observations/analyses can clarify the deformation mechanisms of impurity-rich ice. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：7月27日（水）10:00-10:50 場所：C301（3階セミナー室） conference object